PERLINDUNGAN HUKUM TERHADAP MENTALLY DEFECTIVE SEBAGAI KORBAN TINDAK PIDANA PERKOSAAAN - Widya Hapsari, Pradita Wanda Zahra Vanrick Adhi Vaundra (GEMA, 2015)
Rape is an act of a person who by force or threat of violence to force a woman have sex with him/her outside of marriage. This criminal act is set in Article 285 of the Criminal Code. It has been arranged on the crime of rape in the Criminal Code is not without obstacles.With normative research methods, the author tries to examine the relationship between a patient mentally defective to be victims of crime susceptibility of rape so that the future can be known what rights she/he could find as a victim and how to prevent it.Patients who have a mentally defective intellectual functioning sluggish many victims of crime one of the Crime of Rape. This is because their shortcomings are easily exploited by those who are not responsible. Someone with mentally defective conflict with the law should be given special protection due to differences in physical, mental and / or both.Special protection is necessary given the mentally defective as crime victims of rape, because of its shortcomings. Patients deemed incapable mentally defective, helpless and do not understand the law because of the low intellectual ability. Therefore these shortcomings, law enforcement officers need to provide special protection and assistance to the mentally defective persons who are victims of crime, particularly crimes of morality.